Investigating the Factors Affecting the Length of Stay of Patients Admitted To Psychiatry Hospital at North of Iran - Pezhman Hadinezhad; Javad Setareh; Mahmood Moosazadeh (علوم بهداشتی ایران)
Background and purpose: Length of stay is one of the most useful indicators, which can be used for aims, such as managing hospital, determining quality of control and available resources of the hospital. Concerning the high prevalence of psychiatric disorders in the community, studying the factors affecting the length of stay of these patients in psychiatric hospitals seemed to be useful and significant. Materials and methods: The present research was a cross-sectional study. The sample consisted of 152 patients with psychiatric disorders hospitalized in the Psychiatry Hospital of Mazandaran University of Medical Sciences. The final diagnosis of psychiatric disorder based on the DSM-V criteria and the length of stay at the end was recorded. The collected data were then analyzed by SPSS Software ver. 16 Results: Length of stay was significantly higher in men than women (p <0.001). In terms of diagnosis, the maximum duration of hospitalization was related to psychotic disorders (p = 0.001), and the length of stay increased significantly 0.21 day for each time of hospitalization. (p=0.008) Conclusion: The length of stay in men with psychotic disorders and more frequent hospitalization was found to be higher than others. Hence, it seemed necessary to consider plans about these patients.